Acrylic denture base repair (part I): Estimations of repair space, profile designs, and residual monomer calibration curve on strength of denture base. - Nadira A Hatim; Mohammed M Sadoon (University of Mosul, College of Dentistry, 2006)
Aims: To estimate the best profile design used for repair at the fractured area, the suitable space to be left between the two fracture pieces, and to determine the percentage of residual monomer calibration curve of heat cured acrylic resin polymerized by water bath. Material and methods: Forty five samples of heat cured acrylic denture base resin were prepared, and repaired by water bath with different profile designs, and different space distances at fractured area, the samples were tested to measure transverse strength. In addition to five samples prepared for determination of the light absorbency of aqueous solution by spectrophotometer. Analysis of variance (ANOVA), and Duncan's multiple range test were used for statistical analysis. Results: showed that there is no significant difference between different profile designs, and no significant differences between repaired samples with 2 and 3 mm space at fracture area. The absorbency of aqueous solution at 0.125-0.005 mg/ml concentration is helpful for this study. Conclusion Repaired specimens showed less transverse strength than control group.Repaired samples with 2 mm repair space and 3 mm repair space were significantly higher than that of 1mm repair space.